Challenges of financing infrastructure projects in the context of financial globalization - Mahmoud, Abdul Muttalib Othman (Arab Journal for Sciences and Research Publishing, 2017)
This research aimed to verify the possibility of the participation of both public and private sectors as well as financial institutions in financing the infrastructure projects. The research also aimed to clarify the effect of the state general financing policies on the financing structure of these projects. The research used the analytical descriptive approach as well as the field study method. The research community, on the other hand, comprised overall external auditors and the statutory auditors of the National Audit Chamber and bankers and employees of the Ministry of Investment and the Ministry of Infrastructure and the Ministry of Finance and National Economy as well as some academic scholars in Sudan. The research distributed a questionnaire form to the sample of the research community, which comprised 210 individuals to collect data using the simple random sample. To effect the appropriate statistical treatments, the research used the statistical package for the social sciences program (SPSS). The research has reached a number of research findings, the most significant of which are the following: Financing the infrastructure projects using the general budget of the state has led to reduce the cost of financing. The success of the infrastructure projects using the appropriate finance methods has encouraged the attraction of finance from the international financial institutions. The lack of stability of the state financing policies has led to the reluctance of the investors and financiers to finance the infrastructure projects. The research then concluded with a set of recommendations, including the following: The research fully recommended developing the methodology of negotiation with the different sources of foreign finance, in order to improve the terms and quality of finance to bring the same into an agreement with the accredited economic principles and strategies.
Keywords: Infrastructure projects; Financial institutions; Financing policies